772 Surgery for Bullous Lung Disease. (12th October 2021) - Mohamed, B; Awad Ahmed, S; Hussein, H; Ahmed, M E A
Abstract: Aim: The aim of this study to assess the surgical presentation and outcome for bullous lung disease in Sudanese patients. Method: A cross sectional hospital based descriptive retrospective study. Procedures were conducted at Al-Shaab Teaching Hospital Sudan during the period from November 2009 to September 2012. Results: 11 patients had lung bullae in the given period. Smoking does not play an important role in the development of bullae in healthy young adults in our patients. Vanishing Lung syndrome (VLS) was seen in 18% of patients without history of smoking. The patients presenting in the fifth decade of life constituted (36.3%) of total number. symptoms of presentation were chest pain and SOB and half of them (45.5%) had exertional dyspnoea. The duration of symptoms before presentation was more than 2 months. Asthma was the only respiratory disease associated seen in 45%. HBV and HTN were the most associated diseases seen in 27% and 18% respectively without significant findings in the history. The diagnosis was made by highresolution CT. Chest in all patients. Bullectomy was done to majority of patients. Muscle sparing thoracotomy is the standard approach (Posterolateral Thoracotomy). improved regarding symptoms and signs (90.9%) and) and no death reported. Conclusions: Bullous lung disease with bilateral lung involvement is common in our patients. However, there was no association between lung bullae and smoking in our population. lt's associated with other respiratory disease. The outcome was excellent, and no death was reported. To prevent the miss diagnosis we need sensitive and noninvasive investigation tools.